8. CASE REPORT: PRE - EXTENSIVELY DRUG - RESISTANT PULMONARY TUBERCULOSIS COMBINED WITH HEPATIC TUBERCULOSIS AT NATIONAL LUNG HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: This article aims to report a case of pre – extensively drug – resistant pulmonary tuberculosis combined with hepatic tuberculosis. The primary goals include contributing to scientific data, as well as sharing insights into the diagnostic and treatment processes.Case report: We describe a 21-year-old female who was admitted to the hospital with symptoms of coughing up yellow sputum, occasionally coughing up small amounts of blood, and fever in the afternoon and evening, with no abdominal symptoms. The patient accidentally discovered peritoneal damage that covers the liver and liver damage by abdominal ultrasound and the diagnosis was confirmed by abdominal magnetic resonance imaging and biopsy of the peritoneal. Histopathological results of the biopsy specimen were granulomatous inflammatory lesions suggestive of tuberculosis. We diagnosed this as a case of pre – extensively drug – resistant pulmonary tuberculosis combined with peritoneal tuberculosis and hepatic tuberculosis. The patient was treated with tuberculosis drugs according to the guidelines of the National Tuberculosis Program and international recommendations. After 10 months of treatment, the patient responded well in terms of clinical symptoms, lesions on chest X-ray and abdominal magnetic resonance imaging.Discussion: The discussion focuses on the epidemiology, the etiology and the treatment of hepatic tuberculosis. In this case, we report about how we can diagnose hepatic tuberculosis based on clinical symptoms; imaging tests; microbiology as well as histopathology tests and treatment response of the patient after 10 months.Conclusion: This is a rare case of pre – extensively drug – resistant pulmonary tuberculosis combined with hepatic tuberculosis.
Keywords: Hepatic tuberculosis; pre – extensively drug – resistant hepatic tuberculosis; pulmonary tuberculosis combined with hepatic tuberculosis.